ANALYSING THE NATIONAL EDUCATION REPORT CARD AS A QUALITY MANAGEMENT INSTRUMENT - Ertanti, Devi Wahyu; Hadi , Syamsul; Kusumaningrum, Shirly Rizki; Seow, Darius (Universitas Islam Malang, 2023)
This research aims to discuss the crucial role of analysing the National Education Report Card as an instrument of education quality management. The focus is on the importance of consistency in deciphering report card data to evaluate student, teacher and overall education policy performance. Through this approach, the article illustrates how appropriate analyses can provide an in-depth view of education trends, identify potential improvements, and support data-driven decision-making. The report also highlights the impact of consistency in research on the efficiency of the national education system, providing a basis for developing more effective strategies to improve learning quality sustainably.